2010
DOI: 10.2353/ajpath.2010.090836
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Regulates Pathologic Angiogenesis by a Eukaryotic Elongation Factor-2 Kinase-Regulated Pathway

Abstract: Abnormal angiogenesis is central to the pathophysiology of diverse disease processes including cancers, ischemic and atherosclerotic heart disease, and visually debilitating eye disease. Resveratrol is a naturally occurring phytoalexin that has been demonstrated to ameliorate and decelerate the aging process as well as blunt end organ damage from obesity. These effects of resveratrol are largely mediated by members of the sirtuin family of proteins. We demonstrate that resveratrol can inhibit pathological angi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 42 publications
4
38
1
Order By: Relevance
“…However, IPA showed that p-38 is related to the Rac1 pathway (Figure 5B). P-38 MAPK (mitogen-activated protein kinase) plays a role in invasion, migration (21, 22) and angiogenesis (23, 24). Based on these data, we focused and started to validate by western blot the proteins involved in the Rac1/p38 pathway shown in blue color in figure 5B.…”
Section: Resultsmentioning
confidence: 99%
“…However, IPA showed that p-38 is related to the Rac1 pathway (Figure 5B). P-38 MAPK (mitogen-activated protein kinase) plays a role in invasion, migration (21, 22) and angiogenesis (23, 24). Based on these data, we focused and started to validate by western blot the proteins involved in the Rac1/p38 pathway shown in blue color in figure 5B.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study reported an inhibitory effect of RSV on CNV development, specifically related to the proliferation of vascular endothelial cells [52]. RSV-induced activation of AMPK results in the phosphorylation of a serine residue of eukaryotic elongation factor 2 (eEF2) kinase, which inactivates eEF2 through threonine phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study on angiogenesis in rat gliomas investigated by color Doppler ultrasound showed that resveratrol-mediated suppression of glioma growth was significantly correlated with the inhibition of macroscopic and microscopic angiogenesis (Chen et al, 2006). A very recent study demonstrated that resveratrol inhibits the proliferation and migration of vascular endothelial cells by activating eukaryotic elongation factor-2 kinase, which in turn phosphorylates and inactivates elongation factor-2, a key mediator of ribosomal transfer and protein translation (Khan et al, 2010). Functional inhibition of the kinase by gene deletion in vivo or RNA as well as pharmacological inhibition completely reverses the effects of resveratrol on blood vessel growth.…”
Section: Angiogenesismentioning
confidence: 97%